Cultural differences in psychological help-seeking attitudes among Asian and Non-Asian University students in Malaysia - Kesantini Athinarayanan Rao; Getrude Cosmas Ah Gang; Carmella Ading (RSIS International, 2025)
This study investigates the impact of culture on psychological help-seeking attitudes among university students in Malaysia, focusing on Asian and Non-Asian cultural groups. A total of 200 students, selected through cluster random sampling, completed the Attitudes Toward Seeking Professional Psychological Help Scale – Short Form (ATSPPH-SF) and the Individualism versus Collectivism Scale (INDCOL). Data were analysed independent t-tests via SPSS 28.0. Findings reveal that while both Asian and Non-Asian students held positive attitudes toward the perceived value and necessity of seeking professional psychological help, both groups showed reluctance regarding openness to seeking help. Cultural differences emerged, with Asian students aligning more with collectivist values and Non-Asian students with individualist values. Significant differences were found in the perception of the value and necessity of professional help. These results suggest the need for culturally tailored interventions to improve help-seeking behaviours, with recommendations for future research exploring the specific support needs of students from different cultural backgrounds. Additionally, the study underscores the importance of developing culture-specific mental health awareness programs to address stigma and educate students on the benefits of seeking psychological help.